Correlation between lactate dehydrogenase and other laboratory data in patients with atopic dermatitis. Issue 4 (2nd February 2022) - Kogawa, Kazuhito; Minakawa, Satoko; Matsuzaki, Yasushi; Okamoto, Asumi; Ogasawara, Shu; Saito, Norihiro; Sawamura, Daisuke
Abstract : Serum lactate dehydrogenase (LDH) can be a clinical marker for assessment of the severity and clinical course of atopic dermatitis (AD). One hundred twenty‐eight patients with AD who visited Hirosaki University Hospital were included in this study. There are positive correlations between LDH and IgE, thymus and activation‐regulated chemokine (TARC), and eosinophils, while TARC and eosinophils are used in evaluating type I‐allergic disease, especially AD, and it is considered that LDH is also useful for evaluation of the severity of AD.